Kaolin Film Increases Gas Exchange Parameters of Coffee Seedlings During Transference From Nursery to Full Sunlight - de Abreu, Deivisson Pelegrino; Roda, Newton de Matos; de Abreu, Gideao Pelegrino; Bernado, Wallace de Paula; Rodrigues, Weverton Pereira; Campostrini, Eliemar; Rakocevic, Miroslava (Frontiers in Plant Science, 2022)
Increases in water use efficiency (WUE) and reduction of negative impacts of high temperatures associated with high solar radiation are being achieved with the application of fine particle film of calcined and purified kaolin (KF) on leaves and fruits of various plant species. KF was applied on young Coffea arabica and Coffea canephora plants before their transition from nursery to full sunlight, during autumn and summer. The effects of KF were evaluated through the responses of leaf temperature (Tleaf), net CO2 assimilation rate (A), stomatal conductance (gs), transpiration (E), WUE, crop water stress index (CWSI), index of relative stomatal conductance (Ig), initial fluorescence (F0) and photosynthetic index (PI) in the first two-three weeks after the plant transition to the full sun. All measurements were performed at midday. In Coffea plants, KF decreased the Tleaf up to 6.7°C/5.6°C and reduced the CWSI. The plants not protected with KF showed lower A, gs, E and Ig than those protected with KF. C. canephora plants protected with KF achieved higher WUE compared to not protected, by 11.23% in autumn and 95.58% in summer. In both Coffea sp., KF application reduced F0, indicating reduced physical dissociation of the PSII reaction centers from the light harvesting system, which was supported with increased PI. The use of KF can be recommended as a management strategy in the transition of Coffea seedlings from the nursery shade to the full sunlight, to protect leaves against the excessive solar radiation and high temperatures, especially in C. canephora during the summer.